POTENSI DAYA TARIK WISATA KAMPUNG RENDANG DI KOTA PAYAKUMBUH - Wulandari, Kiki Rilia; Waryono, Waryono; Pasaribu, Pasaribu (Journal of Home Economics and Tourism, 2017)
This research is a made to describe of atrraction making rendang at Kampung Rendang Kota Payakumbuh reviewed from ingredients, equipments, processing techniques and packaging.This research was descriptive research with qualitative data. The sampling technique was done by purposive sampling, data were collected by observation, interview and documentation involving informans and respondents. According to the research, the authors found that (1) Ingredients use to made rendang and derived from Kampung Rendang are coconuts, coconut pulps, coconut shells, (2) Equipments use to production process are coconut grated machine, coconutmilk squeezer machine, egg beater machine, furnace,crock, spoon stirrer, gas stove, kacik (traditional coconutmilk squeezer), steamer box, vacuum sealer machine, manual packaging machine,(3) Processing techniques rendang are grated coconuts, squeezee coconutmilk, mix an eggs, fire furnace, made rendang, squeeze of rendang`s oil (4) Packaging for rendang using bottle, using plastic with vacuum sealer machine, and also using plastic with manual packaging machine.Keywords: Potention, Tourist Attraction, Kampung Rendang